Distribution of self-reported borderline personality disorder traits symptoms in a large-scale clinical population - Lin, Yong; Guo, ZiLei; Zhou, Yong; Wei, YanYan; Xu, LiHua; Tang, XiaoChen; Wang, Zixuan; Hu, YeGang; Wang, JiJun; Mei, Yi; Wu, HaiSu; Luo, YanLi; et al. (Frontiers in Psychiatry, 2024)
Borderline Personality Disorder (BPD) traits play a crucial role in the prognosis of psychiatric disorders, as well as in assessing risks associated with negativity and impulsivity. However, there is a lack of data regarding the distribution characteristics of BPD traits and symptoms within clinical populations. A total of 3015 participants (1321 males, 1694 females) were consecutively sampled from outpatients at the psychiatric and psycho-counseling clinics at the Shanghai Mental Health Center. BPD symptoms were assessed using a self-reported personality diagnostic questionnaire. Having BPD traits is defined as having five or more positive items in self-reported BPD characteristics. Participants were stratified into male and female groups, age groups, and diagnostic groups (schizophrenia, mood disorders, anxiety disorders). Exploratory factor analysis using principal components analysis was conducted. Three factors were identified: "F1: Affective Instability and Impulsivity", "F2: Interpersonal Unstable and Extreme Reactions", and "F3: Identity Disturbance". Among 3015 participants, 45.9% of the patients self-reported BPD traits. Comparing of male and female patients, there was no statistically significant difference in the occurrence rate of BPD traits (χ 2 =1.835, p=0.176). However, in terms of symptoms, female patients reported more symptoms than male patients. Female patients also exhibited more pronounced features on F2 compared to male patients (t =-1.972, p=0.049). There is a general decrease in BPD traits, symptoms, and factors with increasing age. Specifically, the proportion of positive BPD traits is approximately halved before the age of 30 and decreases to around one-third after the age of 30. BPD traits were most common in the Mood Disorders group at 55.7%, followed by the Anxiety Disorders group at 44.4%, and Schizophrenia group at 41.5% (χ 2 =38.084, p<0.001). Our study revealed the pervasive presence of BPD traits and symptoms among psychiatric outpatients, exhibiting distinctive distributions across gender, age, and diagnostic categories. These findings emphasize the significance of identifying and addressing BPD pathology in the clinical care of psychiatric outpatients.